Viral recognition by the innate immune system : the role of pattern recognition receptors (2010)
ABSTRACT: Pattern recognition receptors are the main sensors of the innate immune response. Their function is to recognize pathogen-associated molecular patterns, which are molecules essential for the survival of microbial pathogens, but are not produced by the host. The recognition of pathogen-associated molecular patterns by pattern recognition receptors leads to the expression of cytokines, chemokines, and co-stimulatory molecules that eliminate pathogens, such as viruses, for the activation of antigen presenting cells and for the activation of specific adaptive immunity. Among the most thoroughly studied pattern recognition receptors implicated in viral infections, there are the toll-like receptors (TLRs) and the RNA helicase-type retinoic acid-inducible gene-1 receptors [or RIG-like receptors (RLRs)]. Moreover, other proteins such as PKR, 2’-5’ OAS, and ADAR also act as effector proteins in antiviral responses. The identification and characterization of pattern recognition receptors have contributed to our knowledge of the role of innate immunity in viral infections and has led us to better understand host-pathogen interactions. The most recent findings concerning the role of TLRs and RLRs in viral infections, the molecular mechanisms of viral ligand recognition through pattern recognition receptors, and the activation of their signaling pathways are discussed in this review.